Measurements and calculations of Ar-broadening parameters of water vapour transitions in a wide spectral region; Molecular Physics; Vol. 115, № 14 - Petrova T. M. Tatjyana Mikhaylovna; Solodov A. M. Aleksandr Mikhaylovich; Solodov A. A. Aleksandr Aleksandrovich; Deichuli V. M. Vladimir Mikhaylovich; Starikov V. I. Vitaly Ivanovich (2017, 2017)
Title screen